Comparison of Vaginal Hysterectomy Techniques and Interventions for Benign Indications: A Systematic Review. Issue 5 (May 2017) - Jeppson, Peter C.; Balgobin, Sunil; Rahn, David D.; Matteson, Kristen A.; Dieter, Alexis A.; Ellington, David R.; Aschkenazi, Sarit O.; Grimes, Cara; Mamik, Mamta M.; Balk, Ethan M.; Murphy, Miles
Abstract : OBJECTIVE: To create evidence-based clinical practice guidelines based on a systematic review of published literature regarding the risks and benefits of available preoperative, intraoperative, and postoperative technical steps and interventions at the time of vaginal hysterectomy for benign indications. DATA SOURCES: We systematically searched the literature to identify studies that compared technical steps or interventions during the preoperative, intraoperative, and postoperative periods surrounding vaginal hysterectomy. We searched MEDLINE, Cochrane Central Register of Controlled Trials, Health Technology Assessments, andClinicalTrials.gov from their inception until April 10, 2016, using the MeSH term "Hysterectomy, Vaginal" and associated text words. We included comparative studies, single-group studies, and systematic reviews published in English. METHODS OF STUDY SELECTION: We double-screened 4, 250 abstracts, identifying 60 eligible studies. Discrepancies were adjudicated by a third reviewer. We followed standard systematic review methodology and the Grades for Recommendation, Assessment, Development and Evaluation approach to evaluate the evidence and generate guideline recommendations. TABULATION, INTEGRATION, AND RESULTS: Because of limited literature, only 16 perioperative risks, technical steps, and interventions were identified: obesity, large uteri, prior surgery, gonadotropin-releasing hormone agonists, vaginal antisepsis, bilateral salpingo-oophorectomy, morcellation, apical closure, uterine sealers, hemostatic injectants, hot cone, retractor, cystoscopy, vaginal packing, bladder management, and accustimulation. We organized and reported these as four domains: patient selection, preoperative, intraoperative, and postoperative. We did not identify any patient characteristics precluding a vaginal approach; chlorhexidine or povidone is appropriate for vaginal antisepsis; vasopressin decreases blood loss by 130 cc; tissue-sealing devices decrease blood loss by 44 cc and operative time by 15 minutes with uncertain complication implications; vertical cuff closure results in 1-cm increased vaginal length; either peritoneum or epithelium can be used for colpotomy closure; and routine vaginal packing is not advised. CONCLUSION: Minimal data exist to guide surgeons with respect to planning and performing a vaginal hysterectomy. This study identifies available information and future areas for investigation. Abstract : A systematic review of available studies is used to develop guidelines for a limited number of technical aspects of vaginal hysterectomy.